An Evaluation of the Non Performing Assets of Public and Private Sector Banks Under the SHG Bank Linkage Programme - Arora, Manpreet; Singh, Swati (Indian Journal of Finance, 2015)
Banking institutions play a significant role in the economic development of a country. There are certain issues of concern that affect their performance and efficiency. One of the major issues is the credit risk involved in the banking sector. According to the Narasimhan Committee, non performing assets (NPAs) are considered as one of the important indicators of profitability and efficiency of any bank. Lesser NPAs indicate a better position of a bank in terms of solvency. More NPAs lead to less profit because of non repayment of interest and principal amount of loan by the creditors, thereby effecting the overall profitability of a bank. Under the Self Help Group (SHG) Bank Linkage Programme (SBLP), the self help groups are linked to a bank where these groups are provided financial services for the benefits of their members. Credit disbursed to a SHG under this scheme is without collaterals. The credit disbursed under this scheme increases the risk for the banks. The main purpose of this study was to compare the public and private sector commercial banks on the basis of NPAs under the SHG Bank Linkage Programme. This paper also tried to study the region wise differences in the amount of NPAs of the public sector banks.